Household Savings: A Survey of Recent Microeconomic Theory and Evidence - Andrew Coleman (New Zealand Government, The Treasury, 1998)
This paper summarises recent theoretical and empirical developments in the vast literature that has examined the microeconomic determinants of household saving. It is designed as a primer to provide a basic understanding of some of the developments in the literature in the last decade. The paper uses the standard intertemporal optimising model as the basic organisational framework, and includes a discussion of precautionary savings, liquidity constraints and bequests. The empirical data is examined in light of this framework. Three key issues related to superannuation provision arise. First, evidence suggests that in most countries households continue to save after retirement. Second, in several countries there is evidence that most people hold very few financial assets at any stage of their lives, and a large number of people hold very few assets, either financial or real. Third, intergenerational transfers appear to provide a motive for the lack of consumption for many of the elderly, particularly the wealthy.
Keywords: 330